PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI CAPCUT DALAM MATERI MENEMUKAN PESAN DARI DONGENG BERGAMBAR UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Nurlaili Nurlaili; Umi Anisa Nur Jannah; Hanif Amrullah; Luthfia Fadilah (Al-mujahidah, 2023)
This research aims to develop an animated video learning media based on the Capcut application for the subject of finding messages in fairy tales and to determine how effective the Capcut-assisted animated video learning media is in increasing student interest in learning at MI Ma'arif Darul Ishlah, Bekri District, Central Lampung Regency. The research and development (R&D) model developed is the 4D model, which is simplified into three stages. The instruments used to collect data are observation, interviews, questionnaires, and documentation. The media development process includes (1) the Define stage, (2) the Design stage, and (3) the Develop stage. A questionnaire is then distributed to measure the increase in student interest in learning. The results of the expert material evaluation showed an average score of 75% with a good category, indicating that the learning media has met the standards for testing. The media experts validated the media with an average score of 75%, indicating that it is suitable for use. The results of the measurement of student interest in learning showed an increase of 76.76% after using the generated media. The animated video learning media based on the Capcut application for the subject of finding messages in illustrated fairy tales meets the criteria and is suitable for use in elementary school learning to increase student interest in learning.